2019
DOI: 10.1093/mnras/stz1725
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical interaction of stellar and planetary winds: effects of charge exchange and radiation pressure on the observed Ly α absorption

Abstract: Lyman α observations of the transiting exoplanet HD 209458b enable the study of exoplanets exospheres exposed to stellar EUV fluxes, as well as the interacting stellar wind properties. In this study we present 3D hydrodynamical models for the stellarplanetary wind interaction including radiation pressure and charge exchange, together with photoionization, recombination and collisional ionization processes. Our models explore the contribution of the radiation pressure and charge exchange on the Lyα absorption p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…Tremblin & Chiang (2013) and Christie et al (2016), using 2D hydrodynamic simulations, argued that the fluctuations of absorption could indicate the variations near the contact surface at relatively high velocities (100 km s −1 ). Esquivel et al (2019) had similar conclusions in 3D simulations. McCann et al (2019) carried out 3D simulations focusing on hot Jupiters and concluded that the Coriolis force and stellar winds are indispensable factors in shaping the asymmetry of planetary outflows (for similar conclusions see also Carolan et al 2020;Shaikhislamov et al 2021).…”
Section: Synergy Between Lyα and He * Observationssupporting
confidence: 74%
See 2 more Smart Citations
“…Tremblin & Chiang (2013) and Christie et al (2016), using 2D hydrodynamic simulations, argued that the fluctuations of absorption could indicate the variations near the contact surface at relatively high velocities (100 km s −1 ). Esquivel et al (2019) had similar conclusions in 3D simulations. McCann et al (2019) carried out 3D simulations focusing on hot Jupiters and concluded that the Coriolis force and stellar winds are indispensable factors in shaping the asymmetry of planetary outflows (for similar conclusions see also Carolan et al 2020;Shaikhislamov et al 2021).…”
Section: Synergy Between Lyα and He * Observationssupporting
confidence: 74%
“…When studying the Lyα outflow for exoplanets, previous studies often attributed transit asymmetry to radiation pressure (e.g., GJ 436b; Bourrier et al 2015Bourrier et al , 2016. Some other studies, using different numerical simulation paradigms, contended that the Lyα radiation pressure is insignificant (e.g., Khodachenko et al 2019 for GJ 436b; Khodachenko et al 2017;Debrecht et al 2020 for HD 209458b), or may have comparable impacts as stellar winds (Esquivel et al 2019;Villarreal D'Angelo et al 2021). A few recent works on He * followed suit on the radiation pressure side: in the EVE simulations of WASP-107b (collisionless particlebased simulations; Allart et al 2018Allart et al , 2019, the authors found that their prescription of radiation pressure accelerates the outflow way too quickly, producing a tail that is directly pointing away from the nightside of the planet.…”
Section: Tail: Stellar Wind or Radiation Pressure?mentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation heats the atmospheres, causing them to inflate and more likely to outflow through a hydrodynamic escape mechanism. While the effects of irradiation on the mass-loss process of exoplanets have been largely studied (Lammer et al 2003; Baraffe et al 2004; E-mail: aline.vidotto@tcd.ie Lecavelier des Etangs et al 2004;Penz et al 2008;Ehrenreich & Désert 2011;Yelle 2004;Tian et al 2005;Garcia Munoz 2007;Murray-Clay et al 2009), and several works have studied how stellar winds interact with escaping atmospheres (Schneiter et al 2007;Khodachenko et al 2012Khodachenko et al , 2015Shaikhislamov et al 2014;Villarreal D'Angelo et al 2014Tripathi et al 2015;Carroll-Nellenback et al 2017;Vidotto et al 2018;Debrecht et al 2019;Daley-Yates & Stevens 2019;Esquivel et al 2019;McCann et al 2019), the effects of stellar ejecta in confining the escape of exoplanetary atmospheres have been less explored. This is the subject of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Sym. HD 2019458 fields (Villarreal D'Angelo et al 2014, 2018, and with or without charge exchange (Esquivel et al 2019), have been able to reproduce the observations. 3D simulations can capture the asymmetric nature of the interaction between the stellar and planetary wind which may leave an imprint in the line profile observed during transit.…”
Section: Stellar Parametersmentioning
confidence: 80%